Penerapan Multimedia Interaktif Untuk Meningkatkan Hasil Belajar PAI Siswa Kelas VIII SMP Negeri 1 Mojotengah Wonosobo Tahun Pelajaran 2023/2024 - Sabila Lailia Ramadhani; Fatkhurrahman Fatkhurrahman; Muhamad Yusuf Amin Nugroho (PT. ALHAFI BERKAH INDONESIA, 2024)
This research aims to: 1) implement interactive multimedia in Islamic Education (PAI) learning at SMP Negeri 1 Mojotengah Wonosobo; 2) determine whether there is an improvement in the learning outcomes of PAI for grade VIII students at SMP Negeri 1 Mojotengah Wonosobo; 3) examine the differences in the learning outcomes of PAI for grade VIII students at SMP Negeri 1 Mojotengah Wonosobo between those who used interactive multimedia and those who did not. This research adopts a quantitative research approach with an experimental method. The design used in this study is a quasi-experimental design with a nonequivalent control group design technique. The research was conducted at SMP Negeri 1 Mojotengah Wonosobo, with a sample of 64 students from classes VIII G and VIII I, divided into two groups: the experimental group and the control group. The instruments used include multiple-choice and short answer test questions as well as documentation. The research results indicate that: 1) The implementation of interactive multimedia in PAI learning for grade VIII students at SMP Negeri 1 Mojotengah Wonosobo; 2) There is an improvement in the learning outcomes of PAI for students using interactive multimedia, with a gain test result of 0.63, which falls into the moderate category and is effective enough for use in learning activities; 3) There are differences in the learning outcomes of PAI students as evidenced by the calculation result of the t-test where tcount > ttable, namely 3.306 > 2.015, thus rejecting Ho and accepting Ha.